Regulation of the retinal determination gene dachshund in the embryonic head and developing eye of Drosophila. - Anderson, J.; Salzer, C.L.; Kumar, J.P. (Developmental Biology, 2006)
The retinal determination gene dachshund is distantly related to the family of Ski/Sno proto-oncogenes and influences the development of a wide range of tissues including the embryonic head, optic lobes, brain, central nervous system as well as the post-embryonic leg, wing, genital and eye-antennal discs. We were interested in the regulatory mechanisms that control the dynamic expression pattern of dachshund and in this report we set out to ascertain how the transcription of dachshund is modulated in the embryonic head and developing eye-antennal imaginal disc. We demonstrate that the TGFbeta signaling cascade, the transcription factor zerknullt and several other patterning genes prevent dachshund from being expressed inappropriately within the embryonic head. Additionally, we show that several members of the eye specification cascade influence the transcription of dachshund during normal and ectopic eye development. Our results suggest that dachshund is regulated by a complex combinatorial code of transcription factors and signaling pathways. Unraveling this code may lead to an understanding of how dachshund regulates the development of many diverse tissue types including the eye.